Pengaruh Usability dalam Self Service Technology Terhadap Kepuasan Pemustaka di Balai Layanan Perpustakaan Unit Grhatama Pustaka Yogyakarta - Aulia Rahma Ritonga (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2022)
Technological advances have an impact on library services. This can be seen from the change in services that were previously manual but now use technology. The existence of technology in circulation services then developed again by presenting self service technology (SST).One of the libraries that implements a self-service system is the Grhatama Pustaka Yogyakarta Library. Grhatama library has visitors who vary in terms of age and status, including students, students and workers. Usability is an attribute used to measure the quality of the interface used by the user. Usability in self-service technology in libraries can be used to determine whether a technology-based service is appropriate and easy to use by users.This study aims to determine the effect of the level of usability in the application of self-service technology on user satisfaction in the library unit Grhatama Pustaka Yogyakarta and users consisting of three groups, namely students, students and workers. Usability consists of effectiveness, efficiency, aesthetic appearance, terminology, navigation, and learnability. This study uses a survey method with a quantitative approach. The research sample was taken using purposive sampling technique. Data collection techniques used are questionnaires, observation, literature study and documentation. The results of this study indicate that there is an effect of usability self service technology on user satisfaction. In addition, there are differences in the level of influence of usability in self service technology on the satisfaction of the three groups of users in this study, namely students, students and workers